Fuel cell gas diffusion layer modification method

By depositing amorphous carbon on the gas diffusion layer of the fuel cell, the problem of difficulty in precise surface structure regulation in the prior art is solved, the contact interface and drainage performance are significantly improved, and the overall performance of the membrane electrode is improved.

CN119864425APending Publication Date: 2025-04-22TAIBIDA TECH (SUZHOU) CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311354713.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-19
Publication Date
2025-04-22

AI Technical Summary

Technical Problem

The surface structure regulation of existing fuel cell gas diffusion layer materials is difficult to accurately control, which affects the performance of the material, especially in terms of contact interfaces and drainage performance.

Method used

By depositing amorphous carbon on the gas diffusion layer, the temperature and time of carbon deposition are adjusted using a combination of oven and deposition furnace to form an optimized surface structure.

Benefits of technology

It effectively improves the contact interface between the gas diffusion layer and the catalytic layer, builds a hydrophilic channel, improves drainage performance, and improves the overall performance of the fuel cell membrane electrode.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119864425A_ABST
    Figure CN119864425A_ABST
Patent Text Reader

Abstract

The invention aims to overcome the defects in the prior art and provide the modification method for the gas diffusion layer of the fuel cell, the method is simple and easy to operate, low in cost and high in manufacturing efficiency and finished product yield, the contact interface of the gas diffusion layer and a catalyst layer can be effectively improved, a hydrophilic channel is constructed to improve drainage, and the performance of a membrane electrode is improved. The specific scheme is as follows: the method for modifying the gas diffusion layer of the fuel cell comprises the following steps: putting a gas diffusion layer raw material with a microporous layer into a drying oven, and setting the temperature of the drying oven to be 110-130 DEG C; the dried gas diffusion layer raw material is placed in a deposition furnace, inert protective gas and carbon source gas are introduced into the deposition furnace, the temperature in the furnace ranges from 600 DEG C to 1200 DEG C, and the deposition furnace is sealed through an inert gas curtain or a furnace door; keeping for a period of time for carbon deposition in the atmosphere of inert gas and carbon source gas; and after deposition is completed, a gas diffusion layer finished product is obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a fuel cell, in particular to a method for modifying a gas diffusion layer of a fuel cell. Background Art

[0002] Proton exchange membrane fuel cell (PEMFC) is a power generation device that uses a proton-conducting polymer membrane as an electrolyte to directly convert the chemical energy in the fuel into electrical energy through an electrochemical reaction.

[0003] The basic structure of PEMFC is mainly bipolar plates (BPP) and membrane electrode assembly (MEA), where the membrane electrode includes cathode, anode and polymer electrolyte membrane (PEM). In the fuel cell, the cathode and anode are usually porous structures, generally referred to as electrodes, and are composed of a gas diffusion layer (GDL) and a catalyst layer (CL). When the battery is running, the reactants enter the catalyst layer through the polar plates and the gas diffusion layer, and electrochemical reactions occur under the action of the electrocatalyst; oxidation reactions occur at the anode, such as hydrogen oxidation reaction (HOR) and methanol oxidation reaction (MOR), and reduction reactions occur at the cathode, usually oxygen reduction reaction (ORR).

[0004] The gas diffusion layer is the core component of the fuel cell, which consists of a large-pore substrate layer and a small-pore microporous layer. The substrate layer provides support for the microporous layer and the catalyst layer, while the microporous layer improves the contact interface between the substrate layer and the catalyst layer.

[0005] At present, the common base layer is a composite carbon paper material, which is made of carbonized fibers such as carbon fiber, wood pulp, cellulose fiber or polyvinyl acid short fiber, mixed into pulp, and then made into carbon paper. The carbon paper is then treated with PTFE for hydrophobicity to form a part of hydrophobic channels, and the common base layer is obtained.

[0006] Theoretically, the thinner the carbon paper is, the shorter the distance that electrons are transferred from the catalyst layer to the bipolar plate, the smaller the resistance, and the more beneficial it is to the output performance of the battery; however, too thin a thickness will result in insufficient support strength, so the thickness of the substrate layer should be as low as possible while maintaining sufficient support characteristics. As for porosity, the greater the porosity, the better the air permeability and the smaller the mass transfer resistance; but on the other hand, too high a porosity will reduce the path for electron transfer and increase resistance. Commercial porosity is generally around 70% to achieve a good performance.

[0007] The substrate layer has high porosity and large pore size. It directly contacts the catalyst layer, which will reduce the effective contact area and increase the contact surface resistance. On the other hand, the catalyst particles in the catalyst layer may fall off and clog the pores, resulting in a reduction in the effective catalytic area and a reduction in gas porosity. Therefore, we need to coat a microporous layer between the substrate layer and the catalyst layer to improve the interface between the substrate layer and the catalyst layer.

[0008] The microporous layer is generally prepared by mixing carbon black powder and PTFE, and then fixed on the base layer by hot pressing, spraying, printing, etc. to form a small pore structure. The pore size and hydrophilicity of the microporous layer are crucial. A microporous layer with excellent performance can effectively increase the contact area with the catalytic layer, reduce the interface resistance, improve the interface electrochemical reaction, and also improve the drainage and gas conduction performance of the base layer.

[0009] However, the surface structure of gas diffusion layer materials cannot be precisely controlled at present, and the differences in surface chemistry of different carbon materials also affect the transmission of matter and electricity. Therefore, seeking a method to improve the surface characteristics of fuel cell gas diffusion layers with easy-to-control product quality, simple process, energy saving and environmental protection has become a key issue that needs to be solved urgently. Summary of the invention

[0010] The purpose of the present invention is to provide a method for modifying the gas diffusion layer of a fuel cell, which is simple and easy to operate, low cost, high production efficiency and finished product yield, and can effectively improve the contact interface between the gas diffusion layer and the catalyst layer, construct a hydrophilic channel to improve drainage, and improve membrane electrode performance.

[0011] The specific plan is as follows: A method for modifying a fuel cell gas diffusion layer, comprising: The gas diffusion layer raw material with the microporous layer is placed in an oven, and the oven temperature is set to 110°C to 130°C; The dried gas diffusion layer raw material is placed in a deposition furnace, an inert protective gas and a carbon source gas are introduced into the deposition furnace, the temperature in the furnace is 600°C to 1200°C, and the deposition furnace is sealed with an inert gas curtain or a furnace door; In an atmosphere of inert gas and carbon source gas, carbon deposition is performed for a period of time; After the deposition is completed, a finished gas diffusion layer is obtained.

[0012] In some embodiments, the raw material of the gas diffusion layer with microporous layer is formed by mixing carbon black powder and PTFE and then fixing them on carbon paper by hot pressing, spraying or printing.

[0013] In some embodiments, the oven drying time is 4 hours or more.

[0014] In some embodiments, the carbon deposition temperature in the deposition furnace is 800-1050°C.

[0015] In some embodiments, the elevated temperature is maintained in the furnace for 30 min to 300 min for carbon deposition.

[0016] In some embodiments, the carbon deposition forms amorphous carbon.

[0017] Furthermore, the mass proportion of the amorphous carbon is about 1-10%.

[0018] Furthermore, the amorphous carbon has a thickness of 5-20 nm.

[0019] In some embodiments, the inert gas includes nitrogen and / or argon, and the carbon source gas is at least one of methane, acetylene, ethylene, propylene, benzene or toluene.

[0020] In some embodiments, the gas diffusion layer raw material is transported by a roll-to-roll transport mechanism with a tension control system.

[0021] Compared with the prior art, the present invention has the following advantages: the present invention effectively deposits amorphous carbon on the gas diffusion layer through the above-mentioned preparation process, effectively improves the contact interface between the gas diffusion layer and the catalyst layer, constructs a hydrophilic channel to improve drainage, and improves the performance of the fuel cell membrane electrode. At the same time, the content and thickness of the deposited amorphous carbon are adjustable, and the gas diffusion layer can be customized according to different use environments. In addition, the bulk resistance and interface contact resistance of the gas diffusion layer can be effectively reduced by carbon deposition. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 This is a process flow chart for preparing fuel cell carbon paper according to the present invention. Example

[0023] The technical solution of the present invention is further described in detail below through embodiments and in combination with the accompanying drawings, but is not limited to the contents of the embodiments. Example 1

[0024] 200 g of a gas diffusion layer raw material with a microporous layer was weighed and placed in an oven with the oven temperature set to 120° C. for heating for 15 h.

[0025] The deposition furnace is introduced with nitrogen protective gas, the dried gas diffusion layer is placed in the deposition furnace, the deposition furnace door is closed and tightened, and the tail gas pipeline is connected; the reaction begins, in the first stage, in the nitrogen atmosphere, the furnace temperature is raised from room temperature to 900°C at a heating rate of 5°C / min; in the second stage, the furnace temperature is maintained at 900°C, acetylene is introduced, and carbon deposition is performed for 1 hour. In the third stage, acetylene is turned off, the temperature is lowered to room temperature in a nitrogen atmosphere, the furnace door is opened, and the finished gas diffusion layer is taken out.

[0026] The amorphous carbon mass accounts for about 3%.

[0027] The amorphous carbon has a thickness of 10 nm. Example 2

[0028] 200 g of a gas diffusion layer raw material with a microporous layer was weighed and placed in an oven with the oven temperature set to 120° C. for heating for 16 h.

[0029] The deposition furnace is fed with nitrogen protective gas, the dried gas diffusion layer is placed in the deposition furnace, the deposition furnace door is closed and tightened, and the tail gas pipeline is connected; the reaction begins, in the first stage, in the nitrogen atmosphere, the furnace temperature is raised from room temperature to 900°C at a heating rate of 5°C / min; in the second stage, the furnace temperature is maintained at 900°C, methane is introduced, and carbon deposition is performed for 1 hour. In the third stage, methane is turned off, the temperature is lowered to room temperature in a nitrogen atmosphere, the furnace cavity is opened, and the finished gas diffusion layer is taken out.

[0030] The amorphous carbon mass accounts for about 3%.

[0031] The amorphous carbon has a thickness of 10 nm. Example 3

[0032] 200 g of a gas diffusion layer raw material with a microporous layer was weighed and placed in an oven with the oven temperature set to 120° C. for heating for 15 h.

[0033] The deposition furnace is fed with nitrogen protective gas, the dried gas diffusion layer is placed in the deposition furnace, the deposition furnace door is closed and tightened, and the tail gas pipeline is connected; the reaction begins, in the first stage, in the nitrogen atmosphere, the furnace temperature is raised from room temperature to 900°C at a heating rate of 5°C / min; in the second stage, the furnace temperature is maintained at 900°C, ethylene is introduced, and carbon deposition is performed for 1 hour. In the third stage, ethylene is turned off, the temperature is lowered to room temperature in a nitrogen atmosphere, the furnace cavity is opened, and the finished gas diffusion layer is taken out.

[0034] The amorphous carbon mass accounts for about 3%.

[0035] The amorphous carbon has a thickness of 10 nm. Example 4

[0036] 200 g of a gas diffusion layer raw material with a microporous layer was weighed and placed in an oven with the oven temperature set to 120° C. for heating for 13 h.

[0037] The deposition furnace is fed with nitrogen protective gas, the dried gas diffusion layer is placed in the deposition furnace, the deposition furnace door is closed and tightened, and the tail gas pipeline is connected; the reaction begins, in the first stage, in a nitrogen atmosphere, the temperature in the furnace is raised from room temperature to 900°C at a heating rate of 5°C / min; in the second stage, the temperature in the furnace is maintained at 900°C, propylene is introduced, and carbon deposition is performed for 1 hour. In the third stage, acrylene is closed, the temperature is lowered to room temperature in a nitrogen atmosphere, the furnace cavity is opened, and the finished gas diffusion layer is taken out.

[0038] The amorphous carbon mass accounts for about 4%.

[0039] The amorphous carbon has a thickness of 12 nm. Example 5

[0040] 200 g of a gas diffusion layer raw material with a microporous layer was weighed and placed in an oven with the oven temperature set to 120° C. for heating for 15 h.

[0041] The deposition furnace is introduced with nitrogen protective gas, the dried gas diffusion layer is placed in the deposition furnace, the deposition furnace door is closed and tightened, and the tail gas pipeline is connected; the reaction begins, in the first stage, in the nitrogen atmosphere, the furnace temperature is raised from room temperature to 900°C at a heating rate of 5°C / min; in the second stage, the furnace temperature is maintained at 900°C, acetylene is introduced, and carbon deposition is performed for 0.5 hours. In the third stage, acetylene is turned off, the temperature is lowered to room temperature in a nitrogen atmosphere, the furnace cavity is opened, and the finished gas diffusion layer is taken out.

[0042] The amorphous carbon mass accounts for about 1%.

[0043] The amorphous carbon has a thickness of 5 nm. Example 6

[0044] 200 g of a gas diffusion layer raw material with a microporous layer was weighed and placed in an oven with the oven temperature set to 120° C. for heating for 15 h.

[0045] The deposition furnace is fed with nitrogen protective gas, the dried gas diffusion layer is placed in the deposition furnace, the deposition furnace door is closed and tightened, and the tail gas pipeline is connected; the reaction begins, in the first stage, in the nitrogen atmosphere, the furnace temperature is raised from room temperature to 900°C at a heating rate of 5°C / min; in the second stage, the furnace temperature is maintained at 900°C, acetylene is introduced, and carbon deposition is performed for 5 hours. In the third stage, acetylene is turned off, the temperature is lowered to room temperature in a nitrogen atmosphere, the furnace cavity is opened, and the finished gas diffusion layer is taken out.

[0046] The amorphous carbon mass accounts for about 10%.

[0047] The amorphous carbon has a thickness of 20 nm. Example 7

[0048] 200 g of a gas diffusion layer raw material with a microporous layer was weighed and placed in an oven with the oven temperature set to 120° C. for heating for 18 h.

[0049] The deposition furnace is fed with nitrogen protective gas, the dried gas diffusion layer is placed in the deposition furnace, the deposition furnace door is closed and tightened, and the tail gas pipeline is connected; the reaction begins, in the first stage, in the nitrogen atmosphere, the furnace temperature is raised from room temperature to 800°C at a heating rate of 5°C / min; in the second stage, the furnace temperature is maintained at 800°C, acetylene is introduced, and carbon deposition is performed for 1 hour. In the third stage, acetylene is turned off, the temperature is lowered to room temperature in a nitrogen atmosphere, the furnace cavity is opened, and the carbon paper is taken out.

[0050] The amorphous carbon mass accounts for about 2%.

[0051] The amorphous carbon has a thickness of 8 nm. Example 8

[0052] 200 g of a gas diffusion layer raw material with a microporous layer was weighed and placed in an oven with the oven temperature set to 120° C. for heating for 15 h.

[0053] Nitrogen protective gas is introduced into the deposition furnace, and the dried gas diffusion layer is placed in the deposition furnace. The gas diffusion layer raw material is transmitted by a roll-to-roll transmission mechanism with a tension control system. The inert gas curtain seal is opened and the exhaust gas pipeline is connected. The length of the deposition furnace is 25 meters.

[0054] The reaction started. In the first stage, the temperature in the furnace was raised from room temperature to 1050°C at a rate of 5°C / min in a nitrogen atmosphere. In the second stage, the temperature in the furnace was kept at 1050°C, acetylene was introduced, and carbon deposition was performed for 1 hour. In the third stage, acetylene was turned off, the temperature was lowered to room temperature in a nitrogen atmosphere, and the finished gas diffusion layer was rolled up.

[0055] The amorphous carbon mass accounts for about 5%.

[0056] The thickness of the amorphous carbon is 15 nm. The resistivity and water contact angle of the obtained gas diffusion layer were tested, and the test data are shown below. Comparative Example

[0057] The resistivity and water contact angle of the gas diffusion layer raw material were tested, and the test data are shown below.

[0058] Surface density / g m-2 Contact surface resistivity / mΩ·cm2 Water contact angle Membrane electrode performance Comparative Example 1 100 8.5 140° <![CDATA[0.668V@2A / cm 2 ]]> Examples 1-4 104-106 7.2-7.4 145° <![CDATA[0.706V@2A / cm 2 ]]> Example 5 102 8.2 140° <![CDATA[0.682V@2A / cm 2 ]]> Example 6 114 7.3 145° <![CDATA[0.685V@2A / cm 2 ]]> Example 7 103 8.0 140° <![CDATA[0.688V@2A / cm 2 ]]> Example 8 108 7.5 145° <![CDATA[0.691V@2A / cm 2 ]]>

Claims

1. A method for modifying a fuel cell gas diffusion layer, characterized in that: The method includes placing a gas diffusion layer raw material with a microporous layer in an oven, and setting the oven temperature to 110°C-130°C; placing the dried gas diffusion layer raw material in a deposition furnace, and introducing an inert protective gas and a carbon source gas into the deposition furnace, and the temperature in the furnace is 600°C-1200°C, and the deposition furnace is sealed with an inert gas curtain or a furnace door; maintaining carbon deposition for a period of time in an inert gas and carbon source gas atmosphere; after completion of deposition, a finished gas diffusion layer product is obtained.

2. A fuel cell gas diffusion layer modification method according to claim 1, characterized in that: The raw material of the gas diffusion layer with microporous layer is formed by mixing carbon black powder and PTFE and then fixing them on carbon paper by hot pressing, spraying and printing.

3. A fuel cell gas diffusion layer modification method according to claim 1, characterized in that: The oven drying time is 4 hours or more.

4. A fuel cell gas diffusion layer modification method according to claim 1, characterized in that: The carbon deposition temperature in the deposition furnace is 800-1050°C.

5. A fuel cell gas diffusion layer modification method according to claim 1, characterized in that: The carbon deposition time in the deposition furnace is 30min~300min.

6. A fuel cell gas diffusion layer modification method according to claim 1, characterized in that: The carbon deposition forms amorphous carbon.

7. A fuel cell gas diffusion layer modification method according to claim 6, characterized in that: The amorphous carbon accounts for 1-10% by mass.

8. A fuel cell gas diffusion layer modification method according to claim 6, characterized in that: The amorphous carbon has a thickness of 5-20 nm.

9. A fuel cell gas diffusion layer modification method according to claim 1, characterized in that: The inert gas includes nitrogen and / or argon, and the carbon source gas is at least one of methane, acetylene, ethylene, propylene, benzene or toluene.